2019
DOI: 10.1186/s12887-019-1769-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of neurodevelopmental disability among infants in eastern Uganda: a population based study

Abstract: BackgroundNeurodevelopmental disability (NDD) is increasingly acknowledged as one of the important causes of disease burden in low income countries. None the less, there is a dearth of data on the burden of NDD and its determinants in these settings. We aimed to establish the prevalence and factors associated with NDD among infants in Eastern Uganda.MethodsWe assessed 487 infants aged 9–12 months within Iganga-Mayuge Health Demographic Surveillance Site in Eastern Uganda using the Malawi Developmental Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…However, in that study social development of those infants was not reported, probably due to the limitations of the assessment tool that was used. In our study, developmental disability among term infants was mainly in the social behavioral domain which is consistent with the findings of our population-based study, confirming that parent–child interactions for optimal development are a challenge in this setting [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in that study social development of those infants was not reported, probably due to the limitations of the assessment tool that was used. In our study, developmental disability among term infants was mainly in the social behavioral domain which is consistent with the findings of our population-based study, confirming that parent–child interactions for optimal development are a challenge in this setting [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…The MDAT tool was validated in Malawi and has sensitivity and specificity of 97% and 82%, respectively, of identifying NDD among children aged 0–6 years in a rural African setting. The research assistants had previously used the MDAT tool for neurodevelopmental assessment in a community-based survey by our team [ 31 ], and an intervention study funded by Saving Brains of Grand Challenges Canada [ 28 ]. In both studies, the same research assistants were trained on how to conduct neurodevelopmental assessment by experts in that field.…”
Section: Data Collectionmentioning
confidence: 99%
“…The participants for this study were the caretakers of babies with NDD identified from a previous cross-sectional population-based study conducted by the same research group [18]. That study assessed 487 children aged 9-12 months to establish the prevalence and associated factors of NDD at population level in the HDSS.…”
Section: Study Setting Design and Participantsmentioning
confidence: 99%
“…Although institutional deliveries in Uganda have increased from 42% in 2006 to 73% in 2016, this has not translated into reduction of neonatal mortality estimated to be 28/1000 in 2006 and 27/1000 live births in 2016 [ 29 , 30 ]. Recent studies also indicate that there is a high prevalence of NDD in the country, and most of the associated factors including asphyxia, post-neonatal complications, and malnutrition among preterm infants are preventable [ 13 , 31 ]. There is currently an increased scale up of neonatal care units in the country but the quality of care provided for management of HRBs to prevent mortality and NDD is not clear.…”
Section: Introductionmentioning
confidence: 99%